Mapping the New Testament : early Christian writings as a witness for Jewish biblical exegesis - Ruzer, Serge. (Jewish and Christian perspectives series, 2007)
This volume discusses links between the exegetical trends current in various Second Temple Jewish circles and patterns of New Testament conversation with Jewish Scripture. The standard focus on Jewish background of Christianity is complemented here by an alternative direction: the "mapping" of New Testament evidence as the early witness to more general trends attested in their fully developed form only later, in rabbinic literature. The question that dominates much of the discussion is: How can the New Testament be used for creating a fuller picture of Second Temple Jewish exegesis? The book deals with a representative variety of samples from different layers of the New Testament tradition: Synoptic Gospels, Pauline Epistles and Acts.